Nonlinear disturbance observer based geometric control of quadrotors. Issue 4 (3rd March 2020) - Sharma, Manmohan; Kar, Indrani
Abstract: This paper proposes a nonlinear disturbance observer based controller (NDOBC) for quadrotors utilizing the rotation matrices for attitude dynamics. The proposed observer does not make the assumption that the disturbance is constant or its upper bound is known. The only assumptions are that the disturbance and its derivatives are bounded and hence can handle constant disturbance as a special case. The proposed disturbance observer can handle large class of disturbances and the NDOBC is shown to be locally input to state stable with respect to the derivatives of the disturbances present in attitude dynamics as well as translational dynamics. The proposed controller as well as the nonlinear disturbance observer has been formulated on the nonlinear manifold SE(3) where the rotational dynamics evolve on SO(3) while the translational dynamics evolve on R 3 . Simulation results as well as implementation on a hardware setup establish the effectiveness of the proposed NDOBC.